A dynamic culture platform enhances the efficiency of the 3D HUVEC‐based tube formation assay. Issue 3 (28th November 2019) - Lovecchio, Joseph; Pannella, Micaela; Giardino, Luciana; Calzà, Laura; Giordano, Emanuele
Abstract: Cell‐based in vitro biological models traditionally use monolayer cell cultures grown over plastic surfaces bathing in static media. Higher fidelity to a natural biological tissue is expected to result from growing the cells in a three‐dimensional (3D) matrix. However, due to the decreased rate of diffusion inherent to increased distances within a tridimensional space, proper fluidic conditions are needed in this setting to better approximate a physiological environment. To this aim, we here propose a prototypal dynamic cell culture platform for the automatic medium replacement, via periodic perfusion flow, in a human umbilical vein endothelial cell (HUVECs) culture seeded in a Geltrex™ matrix. A state‐of‐the‐art angiogenesis assay performed in these dynamic conditions showed sizable effects with respect to conventional static control cultures, with significantly enhanced pro‐(dual antiplatelet therapy [DAPT]) and anti‐(EDTA) angiogenic compound activity. In particular, dynamic culture conditions (a) enhance the 3D‐organization of HUVECs into microtubule structure; (b) accelerate and improve endothelial tube formation by HUVECs in the presence of DAPT; (c) are able to completely revert the blocking effects of EDTA. These evidence emphasize the need of setting proper fluidic conditions for a better approximation of a physiological environment as an appropriate evolution of current cell culture paradigms. Abstract : Cell‐based in vitro biological models traditionally use monolayer cell cultures grown over plastic surfaces bathing in static media. Higher fidelity to a natural biological tissue is expected to result from growing the cells in a three‐dimensional matrix.